Effect of a topical copper indomethacin gel on inflammatory parameters in a rat model of osteoarthritis - Yassin NZ; El-Shenawy SM; Abdel-Rahman RF; Yakoot M; Hassan M; Helmy S (Dove Medical Press, 2015)
Nemat Z Yassin,1 Siham M El-Shenawy,1 Rehab F Abdel-Rahman,1 Mostafa Yakoot,2 Mohamed Hassan,3 Sherine Helmy4 1Department of Pharmacology, National Research Center, Cairo, Egypt; 2Green Clinic and Research Center, Alexandria, Egypt; 3Department of Chemistry, Faculty of Science, Alexandria University, Alexandria, Egypt; 4European Egyptian Pharmaceutical Industries, Alexandria, Egypt Objective: We aimed to investigate the effect of topical application of a Copper indomethacin (Cu-Indo) gel preparation on monosodium iodoacetate (MIA) induced arthritis of the knee joint of rats and to test our hypothesis that copper complex of indomethacin could be a more potent anti-inflammatory agent than its parent compound. Methods: After induction of osteoarthritis by the intracapsular injection of 50 µL with 40 mg/mL MIA, we compared the anti-inflammatory efficacy and safety of a topical application of 1% indomethacin gel in a dose of 1 g/kg of the gel (equivalent to 10 mg/kg of the active substance) daily for 3 weeks versus three decremental dose levels of Cu-Indo gel: an equivalent dose, half the dose, and 25% of the dose of indomethacin. Anti-inflammatory efficacy was assessed in all treated groups by measurement of serum inflammatory cytokines: interleukin 6, interleukin 8, and tumor necrosis factor alpha; and by the weekly assessment of knee joint swelling. Joint mobility and motor coordination were also assessed once weekly by the accelerating rotarod apparatus; histopathological examination of affected joints was also performed. Safety of topical application of Cu-Indo (0.25, 0.5, and 1 g/kg) for up to 3 months to rats’ skin was determined by the estimation of a complete blood count, liver and kidney functions, and histopathologic examination for target tissues. Results: Cu-Indo gel at lower doses was superior to or at least as effective as its parent substance, indomethacin, in most of the studied parameters of inflammation. The lowest tested dose of Cu-Indo, corresponding to 25% of the parent substance indomethacin, exhibited the highest efficacy in reducing the elevated serum-tested interleukins and in increasing the time of duration on the rotarod test, whereas its effect on reduction of edema and tumor necrosis factor alpha was comparable to that of the others. After 3 months of daily application, there were no notable changes in studied safety parameters with the lowest Cu-Indo dose, but the group treated with the higher dose showed a small but statistically significant increase in serum-unconjugated bilirubin and a slight decrease in hemoglobin levels, red blood cells, and platelet count, with normal indices denoting a slight hemolytic effect at the highest dose. Conclusion: Cu-Indo gel has potent anti-inflammatory activity against joint inflammation in the MIA-treated rat model of osteoarthritis at doses of 0.25, 0.5, and 1 g/kg. The lowest studied dose was better on both safety and efficacy parameters. Keywords: osteoarthritis, copper indomethacin gel, monosodium iodoacetate, rats